To evaluate the role of MRI in infants with suspected hypoxic ischemic encephalopathy and prognosticating neurological outcome at end of one year - Ramachandran, Shreyas; Sripathi, Smiti (International Journal of Research in Medical Sciences, 2017)
Background: Hypoxic ischemic encephalopathy (HIE) is one the common causes of neonatal fatality due to perinatal asphyxia. The long-term outcomes of HIE are impaired mental and motor development, hearing loss, recurrent seizures and cerebral palsy. MRI is increasingly becoming the gold standard in diagnosis of HIE as it involves no radiation and can be performed during a neonates physiological sleep. To evaluate the role of MRI in infants with suspected hypoxic ischemic encephalopathy in prognosticating neurological outcomes at end of one year. Methods: A total of 50 patients were included in the study who underwent MRI of brain. A clinical follow up was done at the end of one year. Results: The sensitivity of MRI in prognosticating clinical outcome was 72% and specificity was 71% while PPV and NPV was 86% and 50% respectively. Conclusions: MRI is a useful modality to assess early changes in HIE and it can prognosticate clinical outcome.